2023
DOI: 10.1111/1462-2920.16326
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics and transcriptional responses of a Red SeaProchlorococcus strain to varying temperatures

Abstract: Prochlorococcus play a crucial role in the ocean's biogeochemical cycling, but it remains controversial how they will respond to global warming. Here we assessed the response to temperature (22–30°C) of the growth dynamics and gene expression profiles of a Red Sea Prochlorococcus strain (RSP50) in a non‐axenic culture. Both the specific growth rate (0.55–0.80 day−1) and cell size (0.04–0.07 μm3) of Prochlorococcus increased significantly with temperature. The primary production released extracellularly ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…The thermophiles, which have reached suitable growth conditions within the given temperature range in this study, their abundance showed a signi cant trend of increasing with temperature. The selective effect caused by rising temperature causes some microbes to be dormant even extinction, such as Prochlorococcus [57], cannot adapt to the high temperature environment, which further led to the decline of the alpha diversity of genes. However, this effect was not observed in the experimental groups.…”
Section: Temperature Can Predict the Increasing Trend Of Carbon Cycli...mentioning
confidence: 99%
“…The thermophiles, which have reached suitable growth conditions within the given temperature range in this study, their abundance showed a signi cant trend of increasing with temperature. The selective effect caused by rising temperature causes some microbes to be dormant even extinction, such as Prochlorococcus [57], cannot adapt to the high temperature environment, which further led to the decline of the alpha diversity of genes. However, this effect was not observed in the experimental groups.…”
Section: Temperature Can Predict the Increasing Trend Of Carbon Cycli...mentioning
confidence: 99%